Reading Literacy In a Multiligual Context: Challenges and Strategies for Senior High School Students In Indonesia (Conference on English Language Teaching, 2024)
This study aims to investigate the types of text-based reading comprehension instruction and reading literacy improvement strategies used with students. The study identifies challenges in implementing reading literacy improvement strategies due to inadequate resources in public high schools and aims to equip high school teachers and curriculum support officers with the necessary skills and training. By using the right strategies, it is expected that students will be more motivated and have better reading skills. The method used in this study is a qualitative approach by conducting interviews with three high school students. The main findings in this study indicate that teachers and students need to engage in reading literacy to meet students' needs and encourage the use of familiar reading comprehension strategies every day. The implications are discussed in this study